2023
DOI: 10.1001/jamanetworkopen.2023.3513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time-Restricted Eating on Nonalcoholic Fatty Liver Disease

Abstract: ImportanceThe efficacy and safety of time-restricted eating (TRE) on nonalcoholic fatty liver disease (NAFLD) remain uncertain.ObjectiveTo compare the effects of TRE vs daily calorie restriction (DCR) on intrahepatic triglyceride (IHTG) content and metabolic risk factors among patients with obesity and NAFLD.Design, Setting, and ParticipantsThis 12-month randomized clinical trial including participants with obesity and NAFLD was conducted at the Nanfang Hospital in Guangzhou, China, between April 9, 2019, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 47 publications
3
49
1
1
Order By: Relevance
“…He et al, 2021;M. He et al, 2022;Headland et al, 2016;Hooshiar et al, 2023;Hutchison et al, 2019;Isenmann et al, 2021;Kunduraci & Ozbek, 2020;Liu et al, 2022;Maroofi & Nasrollahzadeh, 2020;McDiarmid et al, 2022;Panizza et al, 2019;Parvaresh et al, 2019;Peeke et al, 2021;Pinto et al, 2020;Pureza et al, 2020;Razavi et al, 2021;Schübel et al, 2018;Steger et al, 2021;Sundfør et al, 2018;Thomas et al, 2022;Trepanowski et al, 2017;X. Wei et al, 2023).…”
Section: Screening Results Of Rctsunclassified
See 1 more Smart Citation
“…He et al, 2021;M. He et al, 2022;Headland et al, 2016;Hooshiar et al, 2023;Hutchison et al, 2019;Isenmann et al, 2021;Kunduraci & Ozbek, 2020;Liu et al, 2022;Maroofi & Nasrollahzadeh, 2020;McDiarmid et al, 2022;Panizza et al, 2019;Parvaresh et al, 2019;Peeke et al, 2021;Pinto et al, 2020;Pureza et al, 2020;Razavi et al, 2021;Schübel et al, 2018;Steger et al, 2021;Sundfør et al, 2018;Thomas et al, 2022;Trepanowski et al, 2017;X. Wei et al, 2023).…”
Section: Screening Results Of Rctsunclassified
“…This study identified 1805 records, of which 38 RCTs involving 3039 participants were included in the NMA (Figure 1) (Antoni et al, 2018; Beaulieu et al, 2021; Bowen et al, 2018; H. Cai et al, 2019; Carter et al, 2016, 2018; Castela et al, 2022; Catenacci et al, 2016; Conley et al, 2018; Coutinho et al, 2018; Erdem et al, 2022; Fagundes et al, 2023; Gabel et al, 2019; Gray et al, 2021; Harvie et al, 2011, 2013; C. J. He et al, 2021; M. He et al, 2022; Headland et al, 2016; Hooshiar et al, 2023; Hutchison et al, 2019; Isenmann et al, 2021; Kunduraci & Ozbek, 2020; Liu et al, 2022; Maroofi & Nasrollahzadeh, 2020; McDiarmid et al, 2022; Panizza et al, 2019; Parvaresh et al, 2019; Peeke et al, 2021; Pinto et al, 2020; Pureza et al, 2020; Razavi et al, 2021; Schübel et al, 2018; Steger et al, 2021; Sundfør et al, 2018; Thomas et al, 2022; Trepanowski et al, 2017; X. Wei et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Intervention studies have shown that TRE could prominently reduce weight and improve metabolic health among people with obesity [10][11][12], metabolic syndrome [13], and diabetes [14,15]. However, trials in patients with NAFLD have been sparse [16,17]. Only one study compared the impacts of TRE (eating only between 8:00 a.m. and 4:00 p.m.) and caloric restriction (CR) on intrahepatic fat and metabolic health among patients with obesity and NAFLD [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, trials in patients with NAFLD have been sparse [16,17]. Only one study compared the impacts of TRE (eating only between 8:00 a.m. and 4:00 p.m.) and caloric restriction (CR) on intrahepatic fat and metabolic health among patients with obesity and NAFLD [17].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Several studies have demonstrated that tRF exerts powerful therapeutic effects on chronic diseases, including obesity, diabetes, cardiovascular diseases, cancer, and neurodegenerative diseases, both in animal models 2,16,17 and humans. 18–21 Moreover, tRF is considered an external cue that profoundly affects the stability of daily biological rhythms, collectively adjusting the circadian rhythm. 22 Continuous glucose monitoring has demonstrated that patients with type-2 diabetes (T2D) adhering to a tRF schedule for 5 days a week can improve blood sugar control.…”
Section: Introductionmentioning
confidence: 99%